Perancangan Tempat Sampah Pemilah Otomatis - Roso, Prasetyo Dewangga Adi; Ramadhan, Fajar Aditya; Saputra, Indra Rizky Fatha; Syamsuddiin, Achmad (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Waste management is still a major challenge in various regions, especially in densely populated urban areas. One of the main problems is the lack of public awareness in sorting waste based on its type, such as organic, inorganic, and metal waste. As a result, waste that should be recycled or reprocessed instead piles up in landfills, polluting the environment, and accelerating ecosystem damage. To overcome these problems, innovative solutions are needed that can help the waste sorting process automatically and efficiently. Microcontroller-based automation technology is one promising approach in this field. Arduino Uno, as one type of microcontroller that is popular and easy to use, allows the design of smart systems with affordable costs and high flexibility.